The Top Ten Errors of Martial Artists Defending Against a Blade - McCurry, John; Grossman, Eliot Lee (Revista de Artes Marciales Asiáticas, 2012)
There are ten deadly errors which make most empty-handed martial-arts techniques against a knife ineffective. The principal error stems from the fact that few present-day martial systems teach the blade. The premise of this article is that to effectively defend against a knife, you need to know how to use one. The purpose of this article is to motivate martial arts instructors to analyze more critically their unarmed knife defense techniques based on a clear understanding of the use of the knife, and to reawaken interest in the blade arts in the martial arts community.